2017
DOI: 10.1158/1078-0432.ccr-16-2842
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab Exposure–Response Analyses of Efficacy and Safety in Previously Treated Squamous or Nonsquamous Non–Small Cell Lung Cancer

Abstract: Purpose: Nivolumab is a fully human IgG4 monoclonal antiprogrammed death-1 antibody with demonstrated efficacy, including durable responses and prolonged survival, in patients with previously treated, advanced non-small cell lung cancer (NSCLC). Exposure-response (E-R) analyses for efficacy and safety were conducted to inform the benefit-risk assessment of nivolumab in this patient population.Experimental Design: The analyses used clinical trial data from patients with squamous (n ¼ 293) or nonsquamous (n ¼ 35… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
111
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 81 publications
(119 citation statements)
references
References 29 publications
(52 reference statements)
8
111
0
Order By: Relevance
“…The practical implications of time‐varying CL confounding nivolumab exposure–response analysis have been described, and it is recommended that exposures after the first dosing cycle be used in exposure–response analyses and using later exposure metrics that can be confounded by treatment effect be avoided. Early exposure metrics after the first cycle of therapy were used to re‐evaluate the exposure‐response (overall survival) for nivolumab, and C avg 1 (C avg after cycle 1) was determined not to be a significant predictor of overall survival, after adjusting for the effect of baseline CL . Baseline CL, independent of C avg 1, was a strong predictor of survival, and patients with MEL with higher baseline CL have a higher risk of death that is independent of systemic drug exposures.…”
Section: Discussionmentioning
confidence: 99%
“…The practical implications of time‐varying CL confounding nivolumab exposure–response analysis have been described, and it is recommended that exposures after the first dosing cycle be used in exposure–response analyses and using later exposure metrics that can be confounded by treatment effect be avoided. Early exposure metrics after the first cycle of therapy were used to re‐evaluate the exposure‐response (overall survival) for nivolumab, and C avg 1 (C avg after cycle 1) was determined not to be a significant predictor of overall survival, after adjusting for the effect of baseline CL . Baseline CL, independent of C avg 1, was a strong predictor of survival, and patients with MEL with higher baseline CL have a higher risk of death that is independent of systemic drug exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous population pharmacokinetic analyses showed that nivolumab clearance appears to be associated with ECOG performance status and albumin level, both of which are related to a patient's disease status . In a nivolumab exposure–response analysis in NSCLC, the magnitude of clearance effect on OS seems to be different in squamous and nonsquamous patients, which may also be related to differences in baseline disease status in these two populations . In addition, among all other tested covariate effects on OS, clearance had the largest impact on OS relative to other covariates, such as ECOG performance status and albumin .…”
Section: Discussionmentioning
confidence: 86%
“…14 Similar results were reported in an exposure-response analysis in NSCLC. 15,16 The parameter estimation of clearance was not highly correlated with other tested covariates, indicating that the effect of clearance on OS was not confounded with other covariates. Furthermore, the influence of such covariates on OS was higher in a model that did not account for the effect of clearance.…”
mentioning
confidence: 93%
See 2 more Smart Citations